Selection of Sewage Treatment Technologies Using Multicriteria Analysis - Teran, Francisco Javier Cuba; Freitas, Elaine Cristina Brás de; Cuba, Renata Medici Frayne; Porto, Victor Hugo Souza Florentino (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
One of the main causes of water body pollution is the discharge of untreated sewage. To reduce this type of pollution, the implementation of sewage treatment systems, especially the unit responsible for managing treatment, is necessary. The selection of sewage treatment technologies is a complex process, as it involves both quantitative and qualitative variables. To achieve the goal defined in this work, which is the selection of sewage treatment technologies applicable to municipalities in the state of Goiás that do not have a sanitary sewage system, the Electre I method was adopted. Multicriteria analysis was used to select the 37 most commonly used sewage treatment technologies in Brazil and define a set composed of the best technology options. For this, three scenarios were defined, in which 16 criteria with technical, economic, social, and environmental characteristics were selected for scenario 1, 10 criteria for scenario 2, and eight criteria for scenario 3. The method was suitable for selecting sewage treatment technologies, with selection for scenario 1 comprising a set of two alternatives (anaerobic pond + facultative pond + maturation pond and slow infiltration); scenario 2 comprising a set of five alternatives (septic tanks, facultative pond, facultative aerated pond, slow infiltration, and UASB reactor), and scenario 3 comprising three alternatives (septic tanks, facultative aerated pond, and UASB reactor).